Helicobacter pylori-Related Extraintestinal Manifestations-Myth or Reality - Cristian Dan Mărginean; Cristina Oana Mărginean; Lorena Elena Meliț (MDPI AG, 2022)
It is well documented that Helicobacter pylori (H. pylori) can cause both gastrointestinal and extraintestinal manifestations. The latter one represents a major burden in terms of diagnosis and treatment. H. pylori-associated systemic subclinical inflammation is mostly responsible for the development of extraintestinal manifestations, and its early eradication might result in preventing all adverse events related to their occurrence. Thus, it was suggested that H. pylori might be associated with iron deficiency anemia, thrombocytopenia (immune thrombocytopenic purpura), Schonlein Henoch purpura, failure to thrive, vitamin B12 deficiency, diabetes mellitus, body mass index, cardiovascular diseases, as well as certain neurological conditions. Nevertheless, studies showed both pros and cons in terms of the role of H. pylori in the development of previously mentioned clinical entity underlining the crucial need for further studies on these topics. Although most of these extraintestinal manifestations occur during adulthood, we must not forget that H. pylori infection is acquired mainly during childhood, and thus its early diagnosis and eradication might represent the cornerstone in the prevention of H. pylori-induced inflammatory status and consequently of all related extraintestinal conditions.